On Modes of Economic Governance - Avinash Dixit (Center for Economic Studies and ifo Institute (CESifo), 2001)
I consider transactions involving asymmetric prisoners' dilemmas between pairs of players selected chosen from two large populations. Games are played repeatedly, but information about cheating is not adequate to sustain cooperation, and there is no official legal system of contract enforcement. I examine how profit-maximizing private intermediation can supply the information and enforcement. I obtain conditions under which private governance can improve upon no governance, and examine why it fails to achieve social optimality.
Keywords: 330